BARRIERS TO THE IMPLEMENTATION OF THE EARLY WARNING SCORE IN THE HOSPITAL TREATMENT ROOM - Ikbal Fradianto; Suhaimi Fauzan; M. Ali Maulana; Yoga Pramana; Nita Arisanti Yulanda; Arief Andriyanto (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Background: Early warning score is one of the tools used by nurses in the treatment room to determine the critical condition of patients undergoing treatment. The early warning score can be a reference for changes in the patient's condition. Nurses have responsibilities, one of which is filling out the early warning score. Seeing the purpose of using the early warning score is very important in its implementation, but in implementing the filling of the early warning score, are there any obstacles felt by nurses. Objective: This research aims to find the barriers to implementing the early warning score in the treatment room. Methods: The method used is descriptive qualitative. The sample in this study was seven nurses in the treatment room. Result: The results of this study are three obstacles in applying the early warning score in the hospital treatment room: It takes a long time, allows for errors in adding up scores, and difficulties in remembering follow-up interventions. Conclusion: This study concludes that there are barriers to implementing the early warning score by nurses in the treatment room. Namely, it takes a long time to apply the early warning score using paper-based. It is possible to add up the scores incorrectly and have difficulty remembering further interventions that must be done.